Comparison of HbA 2, E, F and Red Cell Parameters in Homozygous HbE with and Without α 0 -Thalassemia Trait - Sakorn Pornprasert (2018)
© American Society for Clinical Pathology 2017. All rights reserved. Objectives To compare levels of HbA 2, HbE, HbF, and red cell parameters (total Hb, PCV, MCV, and MCH) and also determine their appropriated cut-off points for initial discrimination between homozygous HbE with and without α 0 -thalassemia trait. Methods Hb analysis results from capillary electrophoresis (CE) and red cell parameters of homozygous HbE without α 0 -thalassemia trait (n = 41) and with α 0 -thalassemia trait (n = 17) were reviewed. Results The MCV, MCH, and HbE of homozygous HbE with α 0 -thalassemia trait were significantly lower than those of homozygous HbE without α 0 -thalassemia, while HbA 2 levels of the former were significantly higher than those of the latter. HbA 2 at a cut-off point of 5.3% had 69.0% efficiency in discrimination between the 2 groups. It could also reduce 56.1% of homozygous HbE samples for α 0 -thalassemia testing. Conclusions The elevated HbA 2 ≥5.3% is a useful marker for initial discrimination between homozygous HbE with and without α 0 -thalassemia trait.